Analysis of Student Satisfaction Level on its Influence in Courses Using Fuzzy Logic - alwendi alwendi; Andi Saputra Mandopa (Salus Publica: Journal of Community Service, 2023)
One of the soft computing technologies that has been widely developed is fuzzy logic. One of the research themes that uses fuzzy logic is the assessment system in research. To do this, an application that can be used to calculate and record the results of lecturers in learning. The purpose of this study is to apply fuzzy logic with the Mamdani method for lecturer research activities at the University of  Graha Nusantara Padangsidimpuan. The steps of the research using the Mamdani method: generating input variables taken from Sinta accredited articles, Simlitabmas grant articles, and articles in international and national journals. generate input variables taken from Sinta accredited articles, Simlitamas grant articles, and articles in international and national journals. In higher education, teachers play an important role in producing skilled and qualified graduates. Therefore, it is necessary to measure student satisfaction with the performance of lecturers at the UGN Padangsidimpuan campus. To determine student satisfaction, observations and questionnaires were distributed to respondents. The questionnaire as a tool and data collection method to measure student satisfaction with lecturer performance is the Mamdani fuzzy logic method.